2010
DOI: 10.1007/s00277-010-1037-7
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG uptake of bone marrow on PET/CT scan: it’s correlation with CD38/CD138 expressing myeloma cells in bone marrow of patients with multiple myeloma

Abstract: The percentage of myeloma cells in bone marrow is subsequently an important index of disease in patients with multiple myeloma (MM). Bone marrow myeloma cells can be detected by strong CD38/CD138 positivity and light scatter characteristics using flow cytometry. The aim of the study was to evaluate the relationship between the degree of F-18 fluorodeoxyglucose (F-18 FDG) uptake and the percentage of CD38/CD138 expressing myeloma cells in the bone marrow of patients with MM. A total of 31 patients with MM (14 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…There was a significant correlation between SUVmax values, bone marrow biopsy cellularity and plasma cell ratios (r=0.54 and r=0.74, P<0.01). Furthermore, in our previous study [10], we found a statistically significant positive correlation between the percentage of CD38/CD138-expressing plasma cells in the bone marrow and both mean qualitative (r=0.616) and semiquantitative (r=0.755) FDG uptake. Recently, Weng et al [33] reviewed the 17 studies in the literature to evaluate the diagnostic accuracy of FDG-PET, PET/ CT, MRI, and scintigraphy for multiple myeloma-related bone disease.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…There was a significant correlation between SUVmax values, bone marrow biopsy cellularity and plasma cell ratios (r=0.54 and r=0.74, P<0.01). Furthermore, in our previous study [10], we found a statistically significant positive correlation between the percentage of CD38/CD138-expressing plasma cells in the bone marrow and both mean qualitative (r=0.616) and semiquantitative (r=0.755) FDG uptake. Recently, Weng et al [33] reviewed the 17 studies in the literature to evaluate the diagnostic accuracy of FDG-PET, PET/ CT, MRI, and scintigraphy for multiple myeloma-related bone disease.…”
Section: Discussionmentioning
confidence: 76%
“…Positron emission tomography (PET)/computed tomography (CT) with fluorine-18 fluorodeoxyglucose (FDG) imaging combines whole-body functional imaging with PET and morphologic imaging with CT in a single study that provides functional information about the rate of glucose metabolism in the body. The basic concept in its application in MM is that malignant plasma cells, that infiltrate the bone marrow, consume much more glucose than normal cells [9][10][11][12]. Many studies [13][14][15] consistently emphasized that F-18 FDG imaging was an accurate and dependable technique in detecting MM osteolytic lesions in a higher number of patients and with greater sensitivity and specificity compared with routinely performed radiographs, bone scan, and CT or MRI.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been further confirmed by F-18 fluorodeoxyglucose positron emission tomography-computed tomography (F-18-FDG PET-CT) scanning. Studies have shown that MM exhibits a high uptake rate of F-18 FDG and is positively correlated with the percentage of CD38/CD138-expressing myeloma cells in the bone marrow (17,18). Moreover, Kaira et al (19) showed that F-18 FDG uptake in cancers is determined by the presence of glucose metabolism, angiogenesis and other factors, suggesting that MM with high rates of F-18 FDG uptake is most likely characterized by increased angiogenesis and glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, regarding semiquantitative evaluations, we performed correlation between results of bone marrow biopsy and both SUV average and SUV max , not only SUV average (Ak et al37 ) or SUV max (Sager et al36 and Haznedar et al39 ). Finally, in comparison to the studies by Sager et al36 and Ak et al,37 our patient population was more homogeneous, involving only primary, nontreated MM patients.…”
mentioning
confidence: 92%
“…The authors found a significant correlation between SUV max from the Their results demonstrated a statistically significant positive correlation between the percentage of CD38/CD138 expressing plasma cells in the bone marrow and both mean qualitative (P = 0.000, r = 0.616) and semiquantitative (P = 0.000, r = 0.755) results of tracer uptake. 37 Haznedar et al 39 found also a significant correlation between bone marrow SUV max of the lesion with the highest 18 F-FDG accumulation and the percentage of bone marrow plasma cell count in 61 newly diagnosed MM patients (r = 0.301, P = 0.024). Our study has some crucial differences from the previously described ones; the major difference is that we performed a combination of dPET/CT acquisition, which led to the acquisition of detailed information regarding 18 F-FDG kinetics, and whole-body static PET/CT, from which the different patterns of bone marrow tracer uptake were identified.…”
mentioning
confidence: 95%